Analysis Of Cash Management Service Quality And Promotions On Customer Loyalty With Customer Satisfaction As A Mediator At PT BNI Senayan Jakarta Region - C. Reynald Putra; Syafri Syafri; Ellyana Amran (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the effect of cash management service quality and promotion on customer loyalty with customer satisfaction as a mediating variable at PT BNI Senayan Jakarta Region. The research method used is quantitative research with data analysis techniques using SEM PLS. The results of the study indicate that the service quality variable has the highest average score in the aspect of the availability of modern banking equipment (3.99) and the lowest in the clarity of information provided to customers (3.86). In the promotion variable, the highest score is in the frequency of advertising promotions that are often carried out (4.18), while the lowest score is in the suitability of promotions to customer targets (4.03). For customer satisfaction, the highest score is found in the customer's desire to recommend the service (4.20) and the lowest in the aspect of bank services and facilities provided (4.10). Customer loyalty has the highest score in the customer's intention to recommend BNI cash management services to friends (4.29) and the lowest score in loyalty not to switch to other services (4.13). Data analysis shows that service quality and promotion have a positive and significant effect on customer loyalty. In addition, customer satisfaction is proven to be a mediating variable that strengthens the relationship between service quality and promotion with customer loyalty. These findings indicate that improving service quality and promotional effectiveness can increase customer satisfaction and loyalty towards BNI cash management services